2014
DOI: 10.1007/s00125-014-3442-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting GLP-1 receptors for repeated magnetic resonance imaging differentiates graded losses of pancreatic beta cells in mice

Abstract: Aims/hypothesisNon-invasive imaging of beta cells is a much-needed development but is one that faces significant biological and technological hurdles. A relevant imaging method should at least allow for an evaluation over time of the mass of beta cells under physiological and pathological conditions, and for an assessment of novel therapies. We, therefore, investigated the ability of a new MRI probe to repeatedly measure the loss of beta cells in a rodent model.MethodsWe developed an innovative nanoparticle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…This demonstrates that exendin-4 probes are b cell specific in the rodent pancreas, which is in line with recent findings. 13,25,26 Besides b cells, the exact pancreatic expression sites of the GLP-1R have been a subject of debate due to conflicting data reported in earlier studies. [27][28][29][30][31][32] Recent studies have demonstrated that many commercially available GLP-1R antibodies are unspecific, and that there exists interspecies variation in pancreatic GLP-1R expression.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that exendin-4 probes are b cell specific in the rodent pancreas, which is in line with recent findings. 13,25,26 Besides b cells, the exact pancreatic expression sites of the GLP-1R have been a subject of debate due to conflicting data reported in earlier studies. [27][28][29][30][31][32] Recent studies have demonstrated that many commercially available GLP-1R antibodies are unspecific, and that there exists interspecies variation in pancreatic GLP-1R expression.…”
Section: Discussionmentioning
confidence: 99%
“…The following structures of the peptides [Nle 14 2 ]Ex(9-39) were designed by Svetlana N. Rylova and Helmut R. Maecke and custom-synthesized by Peptide Specialty Laboratories. The purity was analyzed using analytic reversed-phase high-performance liquid chromatography on an analytic 120-5 C18 Nucleosil column, with a linear gradient of 15%-90% solvent B in 25 min at a flow rate of 1 mL/min (solvent A, 0.1% trifluoroacetic acid/H2O; solvent B, 0.1% trifluoroacetic acid/acetonitrile).…”
Section: Peptides and Radiochemistrymentioning
confidence: 99%
“…Naturally occurring GLP-1 receptor agonist GLP-1(7-36)NH 2 was used as an internal reference, and agonist [Nle 14 ,Lys 40 (Ahx-DOTA-68 Ga)NH 2 ]Ex-4, validated for insulinoma imaging in patients (15), was used as a reference for biodistribution studies ( Table 1). The lowest IC 50 values were found for the 2 agonists [Nle 14 ,Lys 40 (Ahx-DOTA)NH 2 ]Ex-4 (0.9 6 0.3 nmol/L) and GLP-1(7-36)NH 2 (1.1 6 0.3 nmol/L).…”
Section: Binding Affinities Of Ex(9-39)-based Tracersmentioning
confidence: 99%
See 2 more Smart Citations